Experiences of top-level nurses - Tracey, Catherine Ann (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2004)
Societal and scientific changes are shaping expectations of the future direction of healthcare delivery. These changes impinge on nursing, forcing it to study itself, to identify its place in the present and future healthcare arena. The purpose of this study was to contribute to the study of nursing by exploring, from their own perspectives, the experiences of top-level nurses holding the formal position of director of nursing. As little research exists to explain or give an understanding of those experiences and the effects of those experiences on top-level nurses, a grounded theory study of this area of nursing was applicable. It was the contention of this study that top-level nursing cannot be studied in isolation from the context in which it functions. Therefore the aim of the study was to examine the experiences of top-level nurses in the context of nursing and the healthcare system, with the objective of discovering and understanding top-level nursing through the lived experiences of directors of nursing.
Keywords: Nursing, Ph.D.; Ph.D. Trinity College Dublin